If - Krasinski, John, 1979-; Blunt, Emily; Reynolds, Ryan; Damon, Matt; Fleming, Cailey; Carell, Steve; Waller-Bridge, Phoebe; Shaw, Fiona; Gossett Jr., Louis; Paramount Home Entertainment (Firm) (Los Angeles, CA : Paramount, 2024)
A young girl who goes through a difficult experience begins to see everyone's imaginary friends who have been left behind as their real-life friends have grown up.
Title from web page.
Originally released as a motion picture in 2024.
Wide screen.
new dvd 2024 summer.
Director, John Krasinski.
Ryan Reynolds, Cailey Fleming, Steve Carell, Emily Blunt, Matt Damon, John Krasinski, Phoebe Waller-bridge, Fiona Shaw, Louis Gossett Jr..
Keywords: Girls -- Juvenile films; Imaginary companions -- Juvenile films; Children's films; Video recordings for the hearing impaired; Fiction films; Motion pictures; Feature films; Animated films; Comedy films